AI-enabled school management dashboards for the early identification of student mental-health risks in secondary schools in the federal capital territory, Abuja - Wilson-Woko, Victoria Chinyere; Nasara, Benjamin; Chukwu, Mary Chinyere; Peter, Joy Abosede; Iyala, Felix Emeka (Journal of Interdisciplinary Studies in Education, 2026)
Adolescent mental health is a growing concern in secondary schools worldwide. In Nigerian schools, systematic mechanisms for the early detection of psychological risk remain limited, with most institutions continuing to rely on informal observation and crisis-driven referrals. This study examined the influence of artificial intelligence (AI)-enabled school management dashboards on the early identification of student mental health risks in selected private secondary schools in the Federal Capital Territory (FCT), Abuja, Nigeria. A descriptive survey research design was adopted. A researcher-developed AISMMH questionnaire, validated by subject experts, was used to generate responses from 472 respondents. Multiple linear regressions revealed that AI-driven data indicators significantly predicted early mental health risk identification.